Moderated Mediation of Organizational Ambidexterity and Knowledge Sharing in SME Performance - Sofyan Ashari Nur; Satrio Tegar Sadewo; Yesica Apriliana Paska; Miftachul Mujib; Ipuk Widayanti (Apik Cahaya Ilmu, 2026)
This study investigates the interrelationships among employee creativity, organizational ambidexterity, knowledge sharing, and SME performance within the context of Indonesia’s creative industries. Grounded in the Resource-Based View (RBV), the research conceptualizes creativity as a valuable human resource, ambidexterity as a dynamic organizational capability, and knowledge sharing as a moderating mechanism that enhances the utilization of these resources. A quantitative hypothesis-testing approach was applied, using data collected from 180 owners and managers of small and medium enterprises (SMEs) in Yogyakarta, Indonesia. Data were analysed through Partial Least Squares Structural Equation Modelling (SEM-PLS), which is appropriate for complex models with latent variables and moderate sample sizes. The results reveal that creativity positively influences ambidexterity, and ambidexterity significantly enhances SME performance. Moreover, knowledge sharing moderates both the relationship between creativity and ambidexterity and between ambidexterity and performance, strengthening their effects. These findings suggest that creativity provides the foundation for ambidextrous behaviour, while knowledge sharing acts as a catalyst that amplifies the transformation of creative ideas into innovative performance outcomes. The study contributes to the literature on organizational learning and dynamic capabilities by highlighting the synergistic role of creativity and knowledge sharing in fostering ambidexterity and competitive advantage in SMEs. Practically, it emphasizes the need for SME leaders to cultivate a knowledge-sharing culture and empower employees to experiment and collaborate, thereby enabling their organizations to remain adaptive and sustainable in rapidly changing environments